Risk Mitigation Analysis and Safety Equipment Against Work Accident Prevention - Mursid, Fadlilah; Herawati , Susi (PT ARRUS Intelektual Indonesia, 2023)
Occupational accidents are a serious problem that can cause injury, disability, or even death for workers in various industries. Therefore, it is important to carry out an in-depth analysis of risk mitigation and the use of safety equipment to prevent work accidents. This study aims to analyze risk mitigation and the importance of applying safety equipment in the context of preventing work accidents. The research method used is a case study with a qualitative approach. The research data was obtained through in-depth interviews with experienced workers, safety managers and other related parties in several companies in different industrial sectors. The research results show that effective risk mitigation plays a crucial role in preventing work accidents. Factors such as risk identification, risk evaluation, and mitigation planning become important elements in a safety strategy. In addition, the role of safety equipment such as helmets, gloves, safety shoes, and other personal protective equipment has proven to be very influential in reducing the risk of injury and accidents. This case study also highlights the importance of training and awareness of workers on the correct use of safety equipment. Lack of understanding and awareness can reduce the effectiveness of safety equipment, thereby increasing the risk of work accidents. Based on the research findings, it is suggested that companies adopt a risk-based approach in identifying and mitigating occupational risks. In addition, regular training on the use of safety equipment should be held to increase workers' awareness and understanding of the importance of safety in the workplace.